Application of multi-locus GWAS for the detection of bruchid resistance loci in cowpea (Vigna unguiculata) - Kpoviessi, Akovognon Dieudonné; CHOUGOUROU, CHÈPO DANIEL (My University, 2022)
Identification of genes associated with bruchid resistance variations in cowpea accessions would help breeders to generate new cowpea cultivars with improved resistance and quality. In this work, 107 cowpea collections from various areas in six countries were phenotyped for their responses to Callosobruchus maculatus and genotyped with Single Nucleotide Polymorphism (SNP) markers. Six multi-locus models Genome Wide Association Study (mrMLM, FASTmrMLM, pKWmEB, pLARmEB, FASTmrEMMA and ISISEM-BLASSO) were used to associate the genotype data to phenotypic cowpea resistance traits: Percentage of Bruchid Emergence (PBE); Percentage of Weight Loss (PWL); Median Development Period (MDP); Dobie Susceptibility Index (DSI); Number of Egg Laid (NEL) and Mean Number of Hole (MNH). Out of 14 QTNs, three were associated with more than one trait and were associated with 11 candidate genes located within 10–30 kb of the QTNs. These candidate genes exhibit functionalities associated with cowpea resistance mechanisms. All these results could contribute to the gene networks in resistant cowpea varieties. The result of this study could also increase our knowledge of genetic resistance of cowpea to bruchids and could be useful for molecular breeding.
Keywords: Callosobruchus maculatus; candidate genes; cowpea varieties; GWAS method; resistant traits